Experimental study of adhesive joints with mechanical interlocking of acrylonitrile butadiene styrene (ABS) parts fabricated for fused filament (FFF) - Molino Alvarez, Erwin; Quintana González, Sergio Andres; Lopez Taborda, Luis Lisandro; Niebles Nuñez, Enrique Esteban (Rapid prototyping journal, 2023)
Purpose Additive manufacturing has disadvantages, such as the maximum part size being limited by the machine’s working volume. Therefore, if a part more considerable than the working volume is required, the part is produced in parts and joined together. Among the many methods of joining thermoplastic parts, adhesives and mechanical interlocking are considered. This study aims to characterize and optimize mechanically stressed adhesive joints combined with female and male mechanical interlocking on acrylonitrile butadiene styrene (ABS) specimens made with fused filament fabrication (FFF) so that the joint strength is as close as possible to the strength of the base material. Design/methodology/approach This study characterized the subject’s state of the art to justify the decisions regarding the experimental design planned in this research. Subsequently, this study designed, executed and analyzed the experiment using a statistical analysis of variance. The output variables were yield strength and tensile strength. The input variables were two different cyanoacrylate adhesives, two different types of mechanical interlock (truncated pyramid and cylindrical pin) and the dimensions of each type of mechanical interlock. This study used simple and factorial experiments to select the best adhesive and interlocking to be optimized using the response surface and the steep ascent method. Findings The two adhesives have no statistical difference, but they show different data dispersion. The design or yield stress was a determining factor for selecting the optimal specimen, with cylindrical geometry exhibiting higher resistance at initial failure. Geometry type is crucial due to the presence of stress concentrators. The cylindrical geometry with fewer stress concentrators demonstrated better tensile strength. Ultimately, the specimen with a mechanically reinforced joint featuring a cylindrical pin of radius 5.45 mm and height of 4.6 mm exhibited the maximum tensile and yield strength. Originality/value Previous research suggests that a research opportunity is the combination of bonding methods in FFF or fused deposition modeling, which is not a frequent topic, and this research to enrich that topic combines the adhesive with mechanically interlocked joints and studies it experimentally for FFF materials, to provide unpublished information of the performance of the adhesive joint with mechanical interlocking, to designers and manufacturers of this technology.